BALANCING PRIVACY RIGHTS AND DATA PROTECTION IN THEAGE OF ARTIFICIAL INTELLIGENCE: A STATISTICAL COMPARATIVE LEGAL FRAMEWORK (Lex localis - Journal of Local Self-Government, 2025)
The widespread use of Artificial Intelligence (AI) across many industries gives rise to substantial privacy apprehensions, necessitating a sophisticated comprehension and smart implementation of privacy safeguards. This essay examines the complex difficulties of protecting privacy in the era of AI, investigating the dynamic relationship between technical progress and privacy standards. AI's ability to gather and analyse large amounts of data increases privacy issues, emphasising the need for transparent and ethical data procedures. The essay highlights the need for decentralised AI platforms and strong legal frameworks in safeguarding privacy, based on the analysis of case studies and regulatory actions. The statement promotes the idea of stakeholders working together to find a balance between the advantages of AI and the protection of privacy rights. The goal is to ensure that AI technologies are developed and used responsibly, with a strong commitment to respecting human privacy and dignity. This project primarily focuses on analysing the implementation of Russian data protection law (RDPL) and US data protection legislation on private firms, public organisations, and institutions, specifically from the standpoint of controllers and processors via survey. The scope of this research is limited to organisations rather than people, owing to the size limitations of this study.